INDICADORES DE ALTAS HABILIDADES/SUPERDOTAÇÃO EM ESTUDANTES DA EDUCAÇÃO SUPERIOR NO PANTANAL SUL-MATO-GROSSENSE - LARISSA TAYNARA DOS SANTOS BRANDÃO (2025)
In the current scenario, it is still common to associate the audience of special education only with individuals who have some form of disability, overlooking the fact that people with giftedness are also part of this group. The lack of knowledge on this subject causes a certain unease for many, among other factors that can create conflicts both for individuals and for the social environment. This misinformation perpetuates false ideas about this group, and such stereotypes can create numerous barriers in their educational, professional, and other aspects of life. It is necessary to expand studies related to higher education, since there are gaps when it comes to the identification process in the university context, from the lack of visibility of these students, to the lack of instruments that aim at identification with the aim of providing support to these subjects. After all, they are present in society and are often unnoticed throughout their journey. In this context, the present study investigated the presence of students with indicators of giftedness in courses offered by a public higher education institution in Corumbá, Mato Grosso do Sul. The research is characterized as both qualitative and quantitative, using field research methodology within the institution. The data collection instruments included sociogram records, the Academic Performance Coefficient (APC) survey, and the application of questionnaires (QIIAHSD – Adults and QIIAHSD – Second Source). In total, 50 students from various courses participated in this study. The analysis was conducted as follows: the sociogram records were analyzed quantitatively through ranking; while the APC analysis was based on the median and interquartile range, considering the third quartile (Q3) as the cut-off point of the values. Regarding the scoring of the QIIAHSD – Adults and QIIAHSD – Second Source questionnaires, the scoring was based on the criteria proposed by the material itself, which involved assigning one (1) point per question. For analyzing these scores, to use the formula that allows obtaining the quartile values for each of the questionnaires and, as in the APC, the cut-off point was Q3. The university setting was chosen for this study as it encompasses an age group that still requires more research regarding this audience in this environment, focusing on adults. The results revealed the presence of students with giftedness indicators in higher education. During the process of analyzing the results, there were students who stood out in one or more instruments applied, however, according to the criteria established in this study to consider those who showed indicators giftedness, it was based on the academics who stood out in three or four of the instruments used. Thus, with the application of more than one instrument and from the procedure of triangulation of the data of each participant, in order to have a detailed perspective of the phenomenon, the result was the number of seven students with strong indicators of giftedness in the university environment, corresponding to 14% of the total participants. In this sense, it is hoped that the implementation of this study will contribute to advancing discussions, reflections, and future research addressing giftedness across different contexts and age groups, as well as help reduce the invisibility of a population that still lacks investigation and educational recognition. Keywords: Higher Education. High-ability. Giftedness. Special Education. Identification.